CAMPAIGN IN OPPOSITION TO PROPOSED CIGARETTE TAX INITIATIVE - PUBLIC AFFAIRS COUNSEL (Tufts Archival Research Center, 2007)
Confidential; Report entitled “Campaign in Opposition to Proposed Cigarette Tax Initiative” prepared by the Public Affairs Council. Portrays the industry's response to the proposed increased cigarette tax in Oregon. Outlines response in several different categories. Summarizes background of firms involved, campaign experience, campaign organization, public opinion research survey, grassroots communication and advertising. Emphasizes that media should receive the greatest percentage of the budget and should receive the greatest focus of the response.